The Determinants oftThe Aggregate Electricity in France - Bismans, Francis; Gnimassoun, Blaise (DEMO, 2017)
This paper mainly aims to study the aggregate electricity demand in the short and long term for France over the period 1990-Q1 to 2015-Q3. To this end, it uses the "General-to-Specific" econometric methodology to estimate an autoregressive distributed lags (ARDL) model. This latest yields a final equation compounded by one cointegrating relation between four variables (electricity consumption, electricity price, gas price and real GDP), and by an error correction mechanism. In the short run, the determinants of electricity demand are essentially made of the occurrence of economic recessions and the variations of temperature.(original abstract)
Keywords: Demand; Electric power; Electric power distribution; Cointegration; Systems diffuse